Unravelling Human Resource Readiness at Cross-Border Postal Services in Serasan - Evandani, Endah; Elmi, Farida (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
Purpose – This study aims to examine the readiness of human resources and the process of placing employees at the Serasan Sea Cross-border Post (PLBN) in Serasan District, Natuna Regency, Riau Archipelago Province. Methodology/approach – This research used a qualitative method with a descriptive approach. Data was collected through in-depth interviews with eight key informants, observations and documentation. Instrument testing was carried out using triangulation and Nvivo12. Findings – The results of the study show that after the inauguration of PLBN Serasan, maximum preparations have been made. The process of placing PLBN employees is a central government policy based on applicable regulations. However, it was discovered that there was a need to identify a more focused PLBN employee needs plan to ensure that the hiring process was on target. The PLBN employee capacity building plan needs to be mapped out properly. It is hoped that more recruitment forms for prospective civil servants for PLBN can be opened. Novelty/value – This study provides an overview of the readiness of human resources and the process of placing employees at PLBN Serasan. The findings of this study can become a basis for the government in planning and adopting policies related to human resource management in other PLBNs. The Serasan PLBN is also considered to have a positive impact on local residents and is expected to contribute significantly to the economic improvement of the Serasan area in the future.